2021
DOI: 10.32799/ijih.v16i1.36021
|View full text |Cite
|
Sign up to set email alerts
|

Gum yan asing Kaangas giidaay han hll guudang gas ga. I Will Never Again Feel That I Am Less Than: Indigenous Health Care Providers’ Perspectives on Ending Racism in Health Care

Abstract: Racism toward Indigenous Peoples continues to permeate throughout the health care system, a reality the authors know all too well in their shared and yet unique personal and professional experiences. Although acknowledging and speaking up against racial injustice is daunting, and is often met with disregard or inaction, the authors contend that this is a necessary undertaking to redress the ongoing harms of colonialism. Correspondingly, those who do not speak up must not have their voices silenced. Instead, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…This study found that structural racism impacts and disrupts access to healthcare through three pathways, including being denied treatment or dismissed, refusal to access care due to fear and distrust in the healthcare system, and the lack of or limited access to healthcare and preventative treatment. These findings align with existing literature, which has widely documented First Nations peoples being dismissed, denied treatment, or receiving substantially lower medical care when accessing healthcare in Canada [30,[45][46][47][48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 88%
“…This study found that structural racism impacts and disrupts access to healthcare through three pathways, including being denied treatment or dismissed, refusal to access care due to fear and distrust in the healthcare system, and the lack of or limited access to healthcare and preventative treatment. These findings align with existing literature, which has widely documented First Nations peoples being dismissed, denied treatment, or receiving substantially lower medical care when accessing healthcare in Canada [30,[45][46][47][48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 88%
“…(29) Instead, adopting an intersectional, culturally safe approach to practice encourages healthcare professionals at the micro level to develop critical inquiry into equity and acknowledge the impact historical and current political, economic and social conditions have on the healthcare system, in order to promote social justice. (27,29,43) Wright, Ballantyne, and Wahoush (44) explain that cultural safety is integral to clinical safety in terms of minimizing risk, practicing reflexivity, and promoting a safe healing environment. As a result, it should be made mandatory for all healthcare professionals to participate in anti-racist, anti-oppressive, culturally safe training prior to being able to practise in institutions, supporting an intersectional approach to treatment and recovery.…”
Section: Micro System Levelmentioning
confidence: 99%
“…As a result, it should be made mandatory for all healthcare professionals to participate in anti-racist, anti-oppressive, culturally safe training prior to being able to practise in institutions, supporting an intersectional approach to treatment and recovery. (14,44,45) A common recurrent theme in Canadian Indigenous health literature is the conceptualization of "culture as cure," the idea that when health interventions are culturally sound and informed, the wellness of Indigenous people including youth are more likely to advance, thereby improving health outcomes and recovery. (14,46,47) For example, VanEvery, Latimer, and Naveau (48) outline the acronym LISTEN (language, individual, share, teachable moments, engage, and navigate) as a clinical strategy to engage with Indigenous youth in a culturally safe way.…”
Section: Micro System Levelmentioning
confidence: 99%
“…Despite the strategies in place to increase admissions, FNMI health professionals and researchers uniformly encounter deleterious systemic forces enacted by the social, historical and geo-political determinants of health (Currie et al, 2012;St. Denis, 2010;Stout et al, 2021) which threaten their success. Structural challenges impede progression through post-secondary studies…”
Section: Introductionmentioning
confidence: 99%
“…This includes a focus on increasing health research capacity to enhance self-determination through policy and service leadership (Cook et al, 2013; Richmond et al, 2013; White et al, 2021). Despite the strategies in place to increase admissions, FNMI health professionals and researchers uniformly encounter deleterious systemic forces enacted by the social, historical and geo-political determinants of health (Currie et al, 2012; St. Denis, 2010; Stout et al, 2021) which threaten their success. Structural challenges impede progression through post-secondary studies shaped by racism, cultural incongruency, pedagogical barriers and financial strain (Currie et al, 2012; Ogilvie & Eggleton, 2011; Shankar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%